Peran Aswaja NU Center dalam pengembangan Moderasi Beragama di Tasikmalaya - Anwar Taufik Rakhmat; Acep Zoni Saeful Mubarok; Ari Farizal Rasyid; Ceceng Saepulmilah (Ikatan Da'i Indonesia, 2026)
This study aims to analyze the role of Aswaja NU Center in Tasikmalaya Regency in developing and disseminating understanding of religious moderation amid the dynamics of community religious life. This research employs a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation study. Research informants include Aswaja NU Center administrators, community leaders, and general public in Tasikmalaya Regency. Data analysis was conducted inductively with source triangulation to ensure validity of findings. Aswaja NU Center Tasikmalaya Regency performs strategic roles through three main approaches: (1) Education and socialization of moderate Ahlusunah Waljama'ah values through Islamic studies, seminars, and training; (2) Development of comprehensive religious literacy by integrating textual and contextual understanding of Islamic teachings; (3) Community empowerment in building tolerance and interfaith harmony. The condition of Tasikmalaya society shows increased religious awareness, but still limited to exoteric aspects with understanding that tends to be partial and exclusive. Aswaja NU Center plays a significant role in strengthening moderate, comprehensive, and contextual Islamic understanding as an effort to counter extremist views. The developed religious moderation emphasizes not only understanding religious texts, but also socio-cultural contexts, resulting in integrative religious attitudes and realizing Islam rahmatan lil'alamin (mercy for all worlds). This research provides practical contributions for religious institutions in designing effective and sustainable strategies for developing religious moderation.